(3GdbGehS GdeUhQ ddUZGQs ((3GdbGgQIs (3TQcI GdYQjS ddceHjhJQs, 2001)
(3jJVef GdcdeGJ GdGSGSjI GdJi jfHZi GdJYQa YdjgG, LejY GdcdeGJ JJhaQ dgG UhQ JOd YdjgG, GdYGH JSGYO Ydi RjGOI GdeaQOGJ hMaXgGs
(3YQHi(B- (3GfLdjRis
(3bGehS eUhQ, GdYGH heSGHbGJ JYdjejIs
windows 98-2000(3, (Bpentium 200mhz(3, (BCd rom+ sound cards
2
Keywords: (3bhGejSs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs